2002
DOI: 10.1002/qua.10094
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of zinc proteinases: A MNDO/d/H study of alternative general‐acid general‐base catalytic pathways for carboxypeptidase‐A

Abstract: ABSTRACT:Two alternative pathways for peptide cleavage by water, both of the general-acid general-base type, have been followed by semiempirical theoretical calculations on a model of the active site. The system of 120 atoms has been carved out of high resolution X-ray coordinates of a carboxypeptidase A (CPA) complex with a ketomethylene inhibitor, pyroglutamic-N-Phe-(CH 2 CO)-Phe-OH. The method employed was a combination of MNDO/d and MNDO/H which, together, enable one to deal with the effect of zinc and of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
22
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…X-ray crystallography and kinetic studies of CPA, together with more advanced theoretical calculations, suggested a contradicting model in which the water molecule is bound to the zinc ion throughout its transformation to the hydroxyl ion. This process is then followed by the binding of the peptide carbonyl to the zinc ion to form a pentacovalent zinc-protein-substrate complex (3,4). Our results provide realtime and direct evidence for the formation of the pentacoordinate catalytic zinc-protein complex during the peptide hydrolysis reaction as proposed by Lipscomb and coworkers (3).…”
Section: Implications For Understanding Protease Reaction Mechanismssupporting
confidence: 74%
See 2 more Smart Citations
“…X-ray crystallography and kinetic studies of CPA, together with more advanced theoretical calculations, suggested a contradicting model in which the water molecule is bound to the zinc ion throughout its transformation to the hydroxyl ion. This process is then followed by the binding of the peptide carbonyl to the zinc ion to form a pentacovalent zinc-protein-substrate complex (3,4). Our results provide realtime and direct evidence for the formation of the pentacoordinate catalytic zinc-protein complex during the peptide hydrolysis reaction as proposed by Lipscomb and coworkers (3).…”
Section: Implications For Understanding Protease Reaction Mechanismssupporting
confidence: 74%
“…1a and SI Text). In this model, the zinc remains tetrahedrally coordinated throughout the reaction (4,14). X-ray crystallography and kinetic studies of CPA, together with more advanced theoretical calculations, suggested a contradicting model in which the water molecule is bound to the zinc ion throughout its transformation to the hydroxyl ion.…”
Section: Implications For Understanding Protease Reaction Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include a cofactor, the divalent zinc ion (Zn 21 ), and a number of specific side groups of the Glu270, Tyr248, Ser197, Asn144, Arg145, Arg127, and Arg71 residues. 3,6,8,[23][24][25][26][27][28] This situation is rather distinct from some other classes of model enzymes such as, e.g., serine hydrolases for which the major mechanistic pattern has been firmly established. 29,30 Among other complexities, extremely diverse kinetic manifestations showing up through the pH profiles, [3][4][5][6]12 inhibition/activation patterns (due to substrates or other effectors), [3][4][5][6]12,13,22 cryospectroscopic (intermediate trapping) experiments, 6,14,16 and viscosity impact observations, [17][18][19] should be mentioned.…”
mentioning
confidence: 96%
“…Interestingly, rather diverse performance has been observed not only between two families of more natural yet synthetic (''probing'') peptide and the counterpart ester (depsi-peptide) substrates but also within the substrates of either of these types that may differ in the chain length and/or residue specificity. [2][3][4][5][6]12,13 The emergence of rapidly progressing powerful computational techniques and two decades of respective serious attempts [23][24][25][26][27] shed some new light on this problem. However, the situation remains in major unclear and definitely requires involvement of additional counterbalancing experimental efforts (vide infra).…”
mentioning
confidence: 99%